Degradation of [Dha7]MC-LR by a Microcystin Degrading Bacterium Isolated from Lake Rotoiti, New Zealand. (27th June 2013) - Somdee, Theerasak; Thunders, Michelle; Ruck, John; Lys, Isabelle; Allison, Margaret; Page, Rachel
Abstract : For the first time a microcystin-degrading bacterium (NV-3 isolate) has been isolated and characterized from a NZ lake. Cyanobacterial blooms in New Zealand (NZ) waters contain microcystin (MC) hepatotoxins at concentrations which are a risk to animal and human health. Degradation of MCs by naturally occurring bacteria is an attractive bioremediation option for removing MCs from drinking and recreational water sources. The NV-3 isolate was identified by 16S rRNA sequence analysis and found to have 100% nucleotide sequence homology with the Sphingomonas MC-degrading bacterial strain MD-1 from Japan. The NV-3 isolate (concentration of 1.0 × 10 8  CFU/mL) at 30°C degraded a mixture of [Dha 7 ]MC-LR and MC-LR (concentration 25  μ g/mL) at a maximum rate of 8.33  μ g/mL/day. The intermediate by-products of [Dha 7 ]MC-LR degradation were detected and similar to MC-LR degradation by-products. The presence of three genes ( mlr A, mlr B, and mlr C), that encode three enzymes involved in the degradation of MC-LR, were identified in the NV-3 isolate. This study confirmed that degradation of [Dha 7 ]MC-LR by the Sphingomonas isolate NV-3 occurred by a similar mechanism previously described for MC-LR by Sphingomonas strain MJ-PV (ACM-3962). This has important implications for potential bioremediation of toxic blooms containing a variety of MCs in NZ waters.